2013
DOI: 10.1259/bjr.20130310
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam CT guidance provides superior accuracy for complex needle paths compared with CT guidance

Abstract: Objective: To determine the accuracy of cone beam CT (CBCT) guidance and CT guidance in reaching small targets in relation to needle path complexity in a phantom. Methods: CBCT guidance combines three-dimensional CBCT imaging with fluoroscopy overlay and needle planning software to provide real-time needle guidance. The accuracy of needle positioning, quantified as deviation from a target, was assessed for inplane, angulated and double angulated needle paths. Four interventional radiologists reached four targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Previous literature concerning CBCT-guided lung and bone biopsies demonstrated that unenhanced pre-procedural CBCT is sufficient to delineate the lesion and enable segmentation [22, 61]. The same could be applied in ablation cases [62]; for difficult lung ablations close to vital structures, a contrast enhancement CBCT may be needed.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Previous literature concerning CBCT-guided lung and bone biopsies demonstrated that unenhanced pre-procedural CBCT is sufficient to delineate the lesion and enable segmentation [22, 61]. The same could be applied in ablation cases [62]; for difficult lung ablations close to vital structures, a contrast enhancement CBCT may be needed.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The remaining 18 studies were evaluated by reading the full text. Of these, 7 were excluded because the subjects enrolled in these studies originated from the same institution or medical center [2228]; 3 were excluded because of insufficient data to construct 2×2 tables of TP, FP, FN, and TN [2931]. As a result, only 8 articles [1421] were included in this meta-analysis, having met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…A small pneumothorax may spontaneously resolve without any treatment. Conversely, patients with large pneumothoraces greater than 30% of the lung volume on chest X-ray or becomes symptomatic should have a chest tube inserted; (II) Hemorrhage (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62): localized hematoma in lungs may resolve without treatment. In a similar manner no special treatment is required if small amount of hemoptysis (e.g., phlegm with blood) occurs.…”
Section: Complicationsmentioning
confidence: 99%